PERFORMATIVITAS GENDER DALAM PENCIPTAAN TARI CAKIL INTERMEDIAL - Eko Supriyanto; R. Danang Cahyo Wijayanto; Muhammad Nurazhariansyah (Universitas Negeri Makassar, 2026)
This article discusses a practice-based study on the creation of an intermedial Cakil dance through a dialogue among the dancer’s body, puppet sabet idioms, and a life-size Cakil figure. Developed through studio work with seven female dancers, the study shows that the puppet functions not merely as a prop but as a choreographic agent that reorganizes weight, arm articulation, ceklekan rhythm, and spatial design. The findings argue that Cakil’s forceful quality can be produced as a technical and kinesthetic achievement rather than as a masculine essence. The article proposes an intermedial creation protocol as a contribution to arts education, creative research, and gender performativity studies.